The evolution of cross-border M&As and innovation strategies: evidence from Chinese construction machinery firms - Lyu, Guoqing; Liefner, Ingo; Schiller, Deniel (ERDKUNDE, 2019)
Cross-border mergers and acquisitions (CBMAs) are an important mechanism of international investment and the configuration of global-local innovation networks. This study offers an evolutionary perspective to understand CBMAs sponsored by Chinese firms by focusing on the key actors and main changes at different stages: a primary stage with the target search process, an initial stage with light-touch integration, a fusing stage with emergence of new entities, and a mature stage with the reorganization of global-local innovation networks. The findings indicate that the innovation strategy of Chinese CBMAs corresponds with the structural integration and differentiation of innovation modes.